2020
DOI: 10.4103/aer.aer_123_19
|View full text |Cite
|
Sign up to set email alerts
|

Normothermia versus hypothermia during cardiopulmonary bypass in cases of repair of atrioventricular septal defect

Abstract: Background: Cardiopulmonary bypass (CPB) used for cardiac surgery is now uniformly carried out under normothermic conditions in adult patients; however, the temperature applied in pediatric CPB vary significantly, ranging from deep hypothermia to normothermia due to the lack of a consistent approach to CPB temperature in pediatric cardiac surgery, which is related to a lack of supportive evidence. Organs protection aim to decrease metabolic requirement and provide energy and oxygen, hypothermia ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…27 Targeted temperature management favoring normothermia during CPB is accompanied by improved tissue perfusion and briefer intubation, shorter ICU stays, and less need for catecholamines. 28 Despite this evidence, DHCA is reserved for complex surgeries; durations of 30 to 40 minutes are considered to be safe. As longer durations can damage the central nervous system, durations should be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…27 Targeted temperature management favoring normothermia during CPB is accompanied by improved tissue perfusion and briefer intubation, shorter ICU stays, and less need for catecholamines. 28 Despite this evidence, DHCA is reserved for complex surgeries; durations of 30 to 40 minutes are considered to be safe. As longer durations can damage the central nervous system, durations should be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…In our CPB temperature management protocol, we found that the influence of hypothermia-induced coagulopathy was not pronounced in the mild hypothermic group compared with other hypothermic CPB patients, as the number of platelets was greater in the former group. Hypothermia has been found to induce thrombocytopenia, inhibit the formation of platelets plugs, or alter the fibrinolytic cascade system [ 32 ]. These factors may lead to blood loss and, consequently, a greater need for blood transfusions [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Como resultado da reação inflamatória global, alterações em diferentes órgãos e sistemas têm sido descritas, incluindo a disfunção cardiopulmonar, a renal, a hepática e a cerebral (143,144). A resposta inflamatória, por outro lado, cursa com gasto energético adicional (145).…”
Section: 5unclassified